Tax accounting in the light of information technology and its impact on revenue collection - Askar, Nasif Jassim Hussein (University of Thi-Qar Journal, 2025)
The research addressed tax accounting in light of digital transformation and its impact on revenue collection. The problem of the research lies in the General Tax Authority relying on traditional methods of tax accounting, which require time, effort, and cost. The research aims to highlight the positive role of information technology, particularly digital transformation, in establishing information bases and facilitating access to them for tax payment. It also aims to reduce cases of tax evasion. Therefore, the research hypothesized that tax accounting in light of digital transformation contributes to alleviating the burden on the taxpayer. To achieve the research objectives and hypotheses, the researcher used a questionnaire method for a sample of employees working in the General Tax Authority/Dhi Qar branch to answer the questionnaire items. Upon analyzing these responses, the researcher reached several conclusions that confirmed the validity of the hypotheses.